Role Of Witness And Victim Protection Agencies For Victims Of Secual Violence - Rosadi, Rosadi; Shodiq, Md.; Pringle , Nisa (CV. Era Digital Nusantara, 2024)
This research aims to analyse the role of the Witness and Victim Protection Agency (LPSK) in providing legal protection to victims of sexual violence in Indonesia. This research uses normative juridical methodology with a qualitative approach to evaluate the effectiveness of protection provided by LPSK in the context of Indonesian law. Based on the findings, the legal protection provided by LPSK is based on clear regulations, including Law No. 13/2006 on Witness and Victim Protection and Law No. 12/2022 on the Elimination of Sexual Violence. However, the effectiveness of the protection is still affected by factors such as limited resources of LPSK, social stigma against victims, and low legal awareness in the community. Therefore, this study recommends increasing the capacity of LPSK, legal counselling, and eliminating social stigma to increase the effectiveness of protection for victims of sexual violence.